Analisis Faktor-Faktor yang Memengaruhi Brand Loyalty Skincare Skintific pada Generasi Z - Citadiantoro, Khafifatuzzahra; Haryanto, Totok; Rachmawati, Erny; Suyoto, Suyoto (Universitas Proklamasi 45, 2025)
This study analyzes the influence of brand experience, brand personality, brand image, and customer experience on brand loyalty in Skintific skincare. The method applied in this study is quantitative. The participants in this study were Gen Z consumers who repurchased Skintific Skincare within the last three months. The number of research samples was 125 respondents. The data collection technique used a questionnaire. The collected data were then analyzed using SMART PLS 3.0. The results of the analysis showed that the five variables, namely brand experience, brand personality, brand trust, brand image, and customer experience, had a positive influence on brand loyalty.